PENGARUH MOTIVASI KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN STUDI PADA DINAS TENAGA KERJA PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA MALANG (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract             Human resources is a very valuable capital for a company because the company's operational activities are run by humans. In this era of globalization, companies need to improve the performance of their employees so that they can compete in the era of globalization. The increase in performance itself is caused by high motivation and organizational commitment. In order to compete in the era of globalization, companies need to pay attention to the performance of their employees. The purpose of this study is to determine the effect of work motivation and organizational commitment on employee performance partially and simultaneously. And the results show that work motivation and organizational commitment have a significant effect on employee performance. The method used in this study is to use quantitative methods by distributing questionnaires to respondents.Keyword : Work motivation, organizational commitment, and employee performance